2009
DOI: 10.1007/s11104-009-9954-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutrient availability from calcareous to acid wetland habitats with closely related brown moss species: increase instead of decrease in N and P

Abstract: To test whether shifts in nutrient availability from calcareous to mineral-poor habitats could be a driving force in the evolution of seven closely related wetland brown mosses, we measured soil and vascular plant nutrients and conducted a laboratory incubation experiment with Swedish and some Dutch samples, in which net N and P-mineralization, respiration and microbial characteristics were measured. In spite of high respiration and microbial N, net N-mineralization appeared to be low for the calcareous Palust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
(76 reference statements)
3
17
0
Order By: Relevance
“…However, net N-mineralization was generally higher on sandstone than on limestone, whether expressed as process rates, per unit C respired or per square metre. This is supported by field and laboratory studies, which reported higher net N-mineralization for acid than calcareous soil as well (Zöttle 1960;Davy and Taylor 1974;Verhoeven et al 1990;Kooijman and Besse 2002;Kooijman et al 2008, Kooijman andHedenäs 2009). Sandstone and limestone also differ in soil texture, but sandy soils had generally higher net N-mineralization than loamy soils as well (Hassink et al 1993;Hassink 1994).…”
Section: Differences In N-cycling Between Speciessupporting
confidence: 55%
See 1 more Smart Citation
“…However, net N-mineralization was generally higher on sandstone than on limestone, whether expressed as process rates, per unit C respired or per square metre. This is supported by field and laboratory studies, which reported higher net N-mineralization for acid than calcareous soil as well (Zöttle 1960;Davy and Taylor 1974;Verhoeven et al 1990;Kooijman and Besse 2002;Kooijman et al 2008, Kooijman andHedenäs 2009). Sandstone and limestone also differ in soil texture, but sandy soils had generally higher net N-mineralization than loamy soils as well (Hassink et al 1993;Hassink 1994).…”
Section: Differences In N-cycling Between Speciessupporting
confidence: 55%
“…Zöttle (1960) and Davy and Taylor (1974) found lower net N-mineralization in calcareous than in acid forest soils, even though they could not explain why. Verhoeven et al (1990) and Kooijman and Hedenäs (2009) measured lower net N-mineralization in base-rich than in acid peatlands, and Kooijman and Besse (2002) in dune grasslands. Naturally, N-availability to the vegetation may not only depend on net N-mineralization in the soil, as plant roots may take up organic N and actively compete with microbes for inorganic N (Schimel and Bennett 2004;Chapman et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Cultivation experiments and more detailed investigations of net nutrient mineralisation (cf. Kooijman and Hedenäs 2009) could cast more light on the detailed habitat requirements of D. trifarius .…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, the N values are a general indication of soil fertility (Ellenberg 1991, Dierssen 2001, Hill et al 2007). Kooijman and Hedenäs (2009) showed, however, that net N and to some degree net P mineralization, and thus plant available N and P compounds, are actually higher in mineral‐poor habitats with a relatively low pH than in mineral‐rich habitats. We considered this information for the assignment of N‐ values to the study species.…”
Section: Methodsmentioning
confidence: 96%
“…It increased in frequency in hummocks in the Jizerské hory Mountains and in both hummocks and hollows in the Hrubý Jeseník Mountains (Table 5). As this species has an optimum in acidic fens with increased net N mineralization (Kooijman & Hedenäs 2009), its increase in permanent plots could be caused by higher nutrient supply through atmospheric deposition. Another explanation for Straminergon stramineum spread could be increased Ca concentration, because this species tolerates moderate Ca content and also grows in the moderately rich fens of the Sphagno‐Tomentypnion alliance (Hájková 2005).…”
Section: Discussionmentioning
confidence: 99%